Early Detection Of Development To Children Aged 0 – 24 Months With Developmental Pre-screening Questionnaire Model Using Certainty Factor Method - Indah Qurrothul Uyun; Wiryawan I Gede; Mukhamad Angga Gumilang; Nugroho Setyo Wibowo (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
An expert system is a computer application designed to help solve specific problems, one of which is the problem of developmental deviations in children aged 0-24 months. This expert system aims to detect early whether the child has deviations from his development by selecting a questionnaire according to the user's baby age. Method, The expert system in this study uses the Certainty Factor. The calculation method aims to determine the percentage of possible developmental deviations in children. This study's results obtained the accuracy of the expert system method of 100% from 75 experiments carried out directly by experts.